Pengaruh E-Service Quality dan Customer Experience Terhadap Repurchase Intention dengan Customer Satisfaction sebagai Variabel Intervening - Surya Chandra; Mohamad Rizan; Shandy Aditya (Jurnal Bisnis, Manajemen, dan Keuangan, 2022)
This study aims to identify the relationship between e-service quality and repurchase intention through customer satisfaction as a mediation, the relationship between customer experience and repurchase intention through customer satisfaction as a mediation, the relationship between customer satisfaction and repurchase intention, the relationship between customer experience and customer satisfaction, and the relationship between e-services. service quality to customer satisfaction for Shopee customers. The data collection method used a questionnaire instrument in the survey method. The object of this research is 243 respondents who are Shopee customers who are domiciled in DKI Jakarta, aged 17 years and over, and have made at least three purchases through the application in the last three months. Data analysis used SEM (Structural Equation Model) in LISREL software version 8.8 in analyzing and processing research data and using SPSS version 25 software. The results of hypothesis testing from this study stated positive results and had a significant effect on all the hypotheses formulated. Penelitian memiliki tujuan untuk mengidentifikasi hubungan hubungan e-service quality terhadap repurchase intention melalui customer satisfaction sebagai mediasi, hubungan customer experience pada repurchase intention melalui customer satisfaction sebagai mediasi, hubungan customer satisfaction terhadap repurchase intention, hubungan customer experience terhadap customer satisfaction, dan hubungan e-service quality terhadap customer satisfaction bagi pelanggan Shopee. Metode pengumpulan data memakai instrumen kuesioner dalam metode survei. Objek penelitian ini yaitu 243 responden yang merupakan pelanggan Shopee yang berdomisili di DKI Jakarta, usia 17 tahun ke atas, dan minimal melakukan tiga kali pembelian melalui aplikasi dalam tiga bulan terakhir. Analisis data memakai SEM (Structural Equation Model) yang ada pada perangkat lunak LISREL versi 8.8 dalam menganalisis dan mengolah data penelitian dan memakai perangkat lunak SPSS versi 25. Hasil uji hipotesis dari penelitian ini menyatakan hasil positif dan berpengaruh signifikan dari semua hipotesis yang dirumuskan.